Identifying Identifying Character Education and Types Of Meaning Of Wise Words in The School Environment - M. Gita Primaniarta; Wahyu Sukartiningsih (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2022)
Character education can be done by giving a wise words that is displayed on the school wall. The existing character education consists of 5 aspects which contain 15 values of character education. This research was conducted using a qualitative descriptive research method that examines the content of character education values in wise words which are analyzed in the study of meaning. The wise words contains 6 values of character education consisting of tolerance values, religious values, discipline values, values for appreciating achievements, values for hard work, and values for responsibility. Found in the semantic meaning, namely narrow meaning. Broad meaning, connotative meaning, emotive meaning, referential meaning, construction meaning, lexical meaning, grammatical meaning, ideational meaning, propositional meaning, central meaning, pictorial meaning, idiomatic meaning. In the wise words, it is found that there is a study of the semantic meaning and the value of character education that is fulfilled according to the identification.